A Comprehensive Analysis of the Wool Supply Chain in Bikaner District of Rajasthan - Ragini Naikoti; Satyveer meena; Anurag Banjare (Indian Journal of Extension Education, 2024)
The study, conducted in the year 2023, investigates the wool supply chain in Rajasthan’s Bikaner district, focusing on marketing methods, challenges, financial viability, and potential improvements. It examines the preferred marketing channels of local farmers, highlights persistent problems, conducts a cost-benefit analysis, and suggests a more efficient supply chain model. Through surveys and interviews, utilizing a multistage sampling technique, data was collected from key stakeholders, including wool producers, traders, processors, and government officials. The findings show that most farmers prefer to sell their wool at wool markets, where they have direct access to buyers. However, challenges such as price fluctuations, delayed payments, and complicated middleman processes continue to affect their earnings. The cost-benefit analysis confirms that wool production in the region is financially sound, with a benefit-cost ratio of 1.38 and a quick payback period of around 1.09 years. To address these issues, a proposed supply chain model, “Producers-Cooperatives-Online Marketplace-Processors-Retailer-Consumer,” was developed, which aims to simplify intermediary problems, strengthen farmers’ bargaining power, open new markets, and increase transparency.